TINJAUAN LOVASTATIN DAN APLIKASINYA - Hardianto, Dudi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2014)
Lovastatin is a drug belonging to statins group that is used to decrease the cholesterol levels in blood. The action mechanism of lovastatinÂ is inhibition of the activity of HMG-CoA reductase enzyme, hence reducing cholesterol production in the liver. Some filamentous fungi produce lovastatin, and Aspergillus terreusÂ is known as the highest lovastatin-producing filamentous fungi, therefore it is generally used for production of lovastatin. Commercial production of lovastatin is based on submerged fermentation. But nowadays solid-state fermentation is becoming an alternative for production of lovastatin. Lovastatin is mainly used for antihypercholeterolemia. Other potential uses of lovastatin include therapy of Alzheimerâs disease, cancer, osteoporosis, Parkinsonâs disease, multiple sclerosis, and rheumatoid arthritis.Keywords: Statin, lovastatin, Aspergillus terreus, fermentation, antihypercholeterolemiaÂ ABSTRAK Lovastatin merupakan obat golongan statin yang digunakan untuk menurunkan kadar kolesterol dalam darah. Mekanisme kerja lovastatinÂ adalah menghambat enzim HMG-CoA reduktase sehingga produksi kolesterol di dalam hati berkurang. Beberapa kapang berfilamen memproduksi lovastatin dan Aspergillus terreusÂ merupakan kapang penghasil lovastatin tertinggi sehingga digunakan dalam produksi lovastatin. Produksi lovastatin secara komersial menggunakan fermentasiÂ cair tetapi sekarang ini fermentasi padat menjadi alternatif lain untuk memproduksi lovastatin. Lovastatin digunakan terutama untuk antihiperkolesterolemia. Lovastatin juga potensial digunakan untuk pengobatan penyakit alzheimer, kanker, osteoporosis, parkinson, multiple sclerosis, dan rheumatoid arthritis.Kata kunci: Statin, lovastatin, Aspergillus terreus, fermentasi, antihypercholeterolemia